Clinical and epidemiological characteristics leptospirosis in the Zaporizhzhia region - Varahabhatla, Vamsi (Запорізький державний медичний університет, 2019)
Leptospirosis, as a natural focal zooanthroponosis, remains an urgent epizootological, epidemiological and ecological problem, as evidenced by the wide spread of the disease in the world and Ukraine, with high morbidity and mortality. The territory of Ukraine in terms of its climatic and geographic conditions is a favorable environment for the existence of natural and atropurgic foci of leptospirosis. The purpose of our study – to analyzed the incidence of leptospirosis based on the materials of Zaporizhzhia Regional Clinical Infectious Disease Hospital” of Zaporizhzhia Regional Council.
Keywords: тези доповідей